Método para medição de utilização de espaços físicos em universidades baseado em modelos industriais - Oliveira, Willian Carneiro de (2020)
Several sectors have sought to quantify the performance of their businesses, with a view to improve the use of available resources. However, the industrial field and the various engineering sectors stand out in this sense, in contrast to the education sector. Considering the growing competition in the educational field, especially for the migration of students to the distance learning modality, universities are being pressured to control and improve the performance of their operations, looking for alternatives in the industrial sector. After all, industries have already successfully used comprehensive performance indicators and methodologies for this purpose. Therefore, the objective of this work is to propose a method, based on industrial models, for measuring the performance of universities, considering the occupation of physical spaces. For this, some reviews on the following topics were carried out: methods used in universities to measure the occupation of physical spaces, performance indicators used in educational institutions, indicators used in industries and the use of these indicators in universities. For its development, the framework called Design Science Research (DSR) was used as methodology. To evaluate the proposed method in the field, an application is carried out in a large private university, located in Curitiba / PR, aiming to measure the occupancy rate of physical spaces. The results of the application of the proposed method were compared with the results of an application simulation with the UFO method, which is one of the methods most used by universities. Among the results obtained with the proposed method are the creation of a standardized basis for measuring the use of spaces, the analysis of the use of classrooms throughout the available time and the consideration of all exceptions registered during this use, which makes the method proposed more accurate than the current method.